Terpenes: Natural Products for Controlling Insects of Importance to Human Health—A Structure-Activity Relationship Study - Dambolena, Jose Sebastian (2016)
Many insects affect food production and human health, and in an attempt to control these insects the use of synthetic insecticideshas become widespread. However, this has resulted in the development of resistance in these organisms, human diseases,contamination of food, and pollution of the environment. Plants natural products and essential oil components such as terpenesand phenylpropenes have been shown to have a significant potential for insect control. However, the molecular properties relatedto their insecticidal activity are not well understood. The purpose of this review is to provide an overview of the toxicity ofterpene compounds against three insects of importance to human health: lice, cockroaches, and Triatominae bugs and to evaluatewhich molecular descriptors are important in the bioactivity of terpenes. For the insects studied, quantitative structure-activityrelationship (QSAR) studies were performed in order to predict the insecticidal activity of terpene compounds. The obtainedQSAR models indicated that the activity of these compounds depends on their ability to reach the targets and to interact withthem.The QSAR analysis can be used to predict the bioactivities of other structurally related molecules. Our findings may providean important contribution in the search for new compounds with insecticidal activity.